Probabilistic oil outflow: the tanker fleet in the context of risk analysis. (1st January 2014) - Ventikos, Nikolaos P.; Sotiralis, Panagiotis
The study of safety and environmental friendliness of tankers remains a vital concern of the shipping industry, and the analysis of risk regarding oil spillage from this type of ships is considered as a top priority item in the agenda of shipping. In this context, the paper is focused on the implementation and probabilistic formulation of regulation 23 of MAPPOL to calculate distribution and quantities of oil outflow for all major oil tanker categories such as Aframax, Suezmax, VLCC, etc. Dedicated databases for each tanker size category have been developed, checked for statistical acceptance, and utilised to obtain all necessary inputs for the calculation of oil outflow. Subsequently, numerous cargo tank configurations per tanker size were examined (for double hull vessels following regulation 19 of MARPOL), multiple scenarios were drafted, and these were put under simulation exercises to come up with oil outflow probabilistic distributions. The paper concludes with a framework for the assessment of costs for (tanker) oil spills.